High Serum Levels of Resistin is Associated With Acute Cerebral Infarction. Issue 2 (March 2022) - Lee, Kee Ook; Lee, Kyung-Yul; Lee, Cheol-Young; Kim, Ji Hoon; Kang, Jaeku; Lee, Hoi Young; Na, Sang-Jun; Oh, Seung-Hun; Heo, Ji Hoe
Abstract : Background: The inflammatory process is involved in the pathogenesis of atherosclerosis and brain tissue injury following cerebral ischemia. Human resistin is a member of small cysteine-rich secreted proteins and has been implicated in inflammatory responses. This study investigated the association of serum resistin level with acute cerebral infarction (ACI). We also investigated its association with the short-term functional outcome. Methods: This study included 106 patients with ACI and 106 age-matched and sex-matched healthy control subjects. Serum resistin level was assessed by using enzyme-linked immunosorbent sandwich assay. The association of serum resistin levels with ACI was analyzed by logistic regression analysis. Results: The serum resistin level was significantly higher in patients with ACI than the control group [median (interquartile range), 35.7 ng/mL (13.0 to 70.5) ng/mL vs. 10.5 ng/ml (15.4 to 16.6), P <0.001]. Logistic regression analysis showed that serum resistin level was associated with an ACI (odds ratio=1.055, 95% confidence interval: 1.035-1.074, P <0.001). Among stroke subtypes, the serum resistin level was higher in the patients with large artery atherosclerosis than those with other subtypes ( P =0.013). High resistin levels were also significantly associated with unfavorable functional outcome at discharge (odds ratio=1.043, 95% confidence interval: 1.024-1.063, P <0.001). Conclusions: This study suggests the potential association of resistin with stroke and cerebral atherosclerosis. Increased serum resistin levels were also associated with early unfavorable neurological outcome.